The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/01.ju.0000094807.95420.fe
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of HLA Class I Antigen Processing Molecules: An Immune Escape Mechanism of Renal Cell Carcinoma?

Abstract: HLA class I APM component abnormalities appear to represent an immune escape mechanism of RCC. This finding emphasizes the need to evaluate the integrity and expression of these molecules in patients with RCC, especially in those selected for treatment with T-cell based immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 18 publications
3
72
0
Order By: Relevance
“…Lower hTERT activity and lower HLA-A*0201 expression by LNCaP cells could thus account for the lesser cytolysis. This result is consistent with findings indicating that tumors can escape immune surveillance by down-regulating HLA (58)(59)(60) or antigen (39,61). It is also notable that the hematologic tumor cells (K562-A2 and SKLY-18) were lysed more effectively than the solid tumors (SK-Mel-29 and LNCaP).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Lower hTERT activity and lower HLA-A*0201 expression by LNCaP cells could thus account for the lesser cytolysis. This result is consistent with findings indicating that tumors can escape immune surveillance by down-regulating HLA (58)(59)(60) or antigen (39,61). It is also notable that the hematologic tumor cells (K562-A2 and SKLY-18) were lysed more effectively than the solid tumors (SK-Mel-29 and LNCaP).…”
Section: Discussionsupporting
confidence: 81%
“…The p865-stimulated T cells exhibited 92% lytic activity of T2 cells pulsed with the p865 peptide, whereas 14% killing was noted of T2 cells loaded with a control HLA-A*0201-restricted peptide for the Wilms' tumor gene (RMFPNAPYL) at an E:T ratio of 50:1. T cells from the same donor stimulated by AAPC A*0201flu containing the minigene for the HLA-A*0201-specific, influenza matrix proteinderived peptide [58][59][60][61][62][63][64][65][66] (GILGFVFTL) generated 4% killing of T2 cells pulsed with p865 peptide at an E:T ratio of 50:1.…”
Section: Resultsmentioning
confidence: 99%
“…A Perier et al to downregulate HLA-I and II genes (Osborne et al, 1997;Atkins et al, 2004;Zagzag et al, 2005). Abnormalities in the expression of HLA molecules altering antigen presentation may contribute to tumors evading the adaptive immune response (Seliger et al, 2000), but promote NK activation.…”
Section: Mutated Vhl Rcc Cells and Nk Cell Activationmentioning
confidence: 99%
“…[4][5][6][7][8] Furthermore, we and other groups have shown that the cytotoxic immune response can fail owing to altered antigen presentation by previous downregulation of APM components. 1,9,10 Surprisingly, little is known about the APM in haematopoietic malignancies, such as acute myeloid leukaemia (AML). Treatment of high-risk or relapsed AML patients is mainly based on the induction of a graft-versus-leukaemia effect after allogenic haematopoietic stem cell transplantation, where donor immune cells recognize minor histocompatibilty antigens on residual blasts and exert a cytotoxic response against leukaemia.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is crucial for recognition of virally infected cells, maintenance of self-tolerance and the surveillance of newly arising tumours by the immune system. 1 The presentation of tumour antigens on MHC class I surface molecules allows cytotoxic T lymphocytes to detect and, subsequently, kill antigen-specific malignant cells. 2,3 Defects in APM have been correlated with enhanced tumour growth and malignancy in solid tumours.…”
Section: Introductionmentioning
confidence: 99%